Efficient light-emitting fluorescent target sheet for ion accelerator beam diagnosis and preparation method of efficient light-emitting fluorescent target sheet

By forming a Fe-Al alloy transition layer and a rare earth doped alumina coating on a stainless steel metal substrate, a high-efficiency fluorescent target sheet was prepared using sol-gel method and heat treatment technology, which solved the low luminescence efficiency and fragile structure of the existing fluorescent targets. The problem of high-precision ion beam diagnosis and specific shape fluorescent target preparation.

CN119290837APending Publication Date: 2025-01-10INST OF MODERN PHYSICS CHINESE ACADEMY OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411528595.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing alumina fluorescent targets have low luminescence efficiency in ion beam detection, are prone to cracking and irradiation damage, and cannot meet the high requirements of fine experiments for beam position measurement. Traditional planar fluorescent targets cannot meet the needs of specific surface spatial distribution.

Method used

Using stainless steel metal substrate, Fe-Al alloy transition layer, alumina layer and rare earth-doped alumina coating, high-efficiency fluorescent target sheets are prepared through sol-gel method and heat treatment technology to form fluorescent coatings with high binding force and high luminescence efficiency Layer, suitable for the preparation of special-shaped parts.

Benefits of technology

It significantly improves the luminescence efficiency and binding force of the fluorescent target, extends the service life, meets the needs of high-precision diagnosis in ion beam fine experiments, and prepares fluorescent targets of specific shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290837A_ABST
    Figure CN119290837A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient light-emitting fluorescent target sheet for ion accelerator beam diagnosis and a preparation method of the efficient light-emitting fluorescent target sheet. The luminous fluorescent target sheet comprises a metal substrate, a Fe-Al alloy transition layer, an aluminum oxide layer and a rare earth doped aluminum oxide coating which are sequentially compounded from bottom to top, the rare earth element doped in the rare earth doped aluminum oxide coating is at least one of Eu, Er, Nd and Sm. By utilizing the method disclosed by the invention, the molecular-level uniform doping of the rare earth elements in the aluminum oxide can be realized. The raw materials used in the sol-gel method are firstly dispersed into a solvent to form a low-viscosity solution, the uniformity of the molecular level is obtained in a very short time, and when gel is formed, the doped trace elements and reactants are uniformly mixed on the molecular level at the same time. The method can be used for preparing the fluorescent target which is high in luminous efficiency, good in fluorescent layer binding force and special in shape and structure, and the requirements of ion beam fine experiments for the special fluorescent target are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-efficiency luminescent fluorescent target sheet for ion accelerator beam diagnosis and a preparation method thereof, belonging to the technical field of accelerator beam diagnosis. Background Art

[0002] Ion accelerators are important tools for studying cutting-edge scientific and technological issues related to nuclear structure, nuclear reactions, preparation of radioisotopes, medical radiotherapy, and material irradiation. The beam diagnostic system can help accelerator device staff to effectively debug the machine and operate the device. The fluorescent target detector is an important beam spot observation device. The fluorescent target can effectively detect the transverse cross-section of the beam by vertically blocking the movement of the beam, giving the shape and area of ​​the beam, and can make a preliminary judgment on the beam intensity and uniformity by fluorescence intensity. Therefore, the fluorescent target has become one of the most widely used basic beam diagnostic detectors due to its convenience and intuitive characteristics. It usually uses the beam to hit special materials such as ceramics, diamonds or yttrium aluminum garnet (YAG) crystals, interact with the atoms in the material, stimulate electron transitions, and the excited state molecules are unstable. They return to the ground state through radiation transitions, emitting visible fluorescence, thereby measuring the position and spatial distribution of the beam.

[0003] Alumina ceramic is a commonly used fluorescent target at present. The thickness of the target sheet can reach several millimeters. When the beam is incident on the target material, during the beam detection, the energetic ion beam bombards the alumina target material. During the interaction between the incident ions and the atoms in the target material, most of the energy is converted into heat energy, resulting in a sharp temperature rise in the target material. The target material has poor toughness and is prone to cracking. At the same time, ions will also cause irradiation damage to the target material and produce a large number of defective structures. These defects will affect the electron transition in the fluorescent target. In addition, since the incident ions carry a large amount of charge and are deposited in the fluorescent target, the conductivity of the target material is poor, and eventually a large amount of charge accumulates on the surface of the target material, damaging the fluorescent target, thereby causing the beam detection to fail. In response to the above problems, depositing a fluorescent coating on the surface of a metal substrate to prepare a coated fluorescent target sheet is a very effective solution. Because the coating is thin, the beam can penetrate the fluorescent layer and be deposited in the substrate, greatly reducing the radiation damage and charge accumulation of the fluorescent layer. In addition, the inside of the metal matrix can be cooled by water (or gas) to quickly remove the heat of ion deposition, so as to prevent the temperature from being too high, causing the target material to expand and break due to thermal stress, thereby greatly improving the service life of the fluorescent target.

[0004] With the advancement of technology, the requirements for ion beam experiments are becoming more and more sophisticated, and the requirements for beam quality are also becoming higher and higher. This also puts higher requirements on the precise control of the beam. The more accurate the measurement of the beam position, the higher the quality of the experimental data, which prompts the beam diagnostic means to be improved accordingly. At present, the ion beam excitation luminescence efficiency of conventional alumina fluorescent targets is low, and it is increasingly unable to meet the needs of fine experiments. In addition, long-term bombardment may also cause fluorescence quenching, and the service life of the fluorescent target is also a very prominent problem. In addition, some special experiments require the investigation of the distribution of the beam in a specific curved surface space, and the traditional planar fluorescent target cannot meet the requirements, and a fluorescent target with a specific concave surface is required. Therefore, the fluorescent coating target prepared by conventional methods is difficult to meet the needs, and it is urgent to develop a method for preparing a coated fluorescent target with high luminescence efficiency and excellent performance. Summary of the invention

[0005] The purpose of the present invention is to provide a highly efficient luminescent fluorescent target sheet for ion accelerator beam diagnosis and a preparation method thereof, so as to meet the needs of ion beam precision experiments.

[0006] The luminescent fluorescent target sheet provided by the present invention comprises, from bottom to top, a metal substrate, a Fe-Al alloy transition layer, an aluminum oxide layer and a rare earth-doped aluminum oxide coating layer which are composited in sequence.

[0007] The material of the metal substrate is stainless steel or other metals with good thermal conductivity; The thickness of the Fe-Al alloy transition layer is 8-500 μm, preferably 50-100 μm; The thickness of the aluminum oxide layer is 100-1000 nm; The thickness of the rare earth doped aluminum oxide coating is 10 μm-500 μm, preferably 20-100 μm.

[0008] The rare earth element doped in the rare earth doped alumina coating is at least one of Eu, Er, Nd and Sm.

[0009] The present invention utilizes the sol-gel method to prepare an aluminum oxide coating doped with some rare earth elements, and combines aluminizing and heat treatment technology to form a Fe-Al transition layer between the doped aluminum oxide layer and the substrate, so as to prepare a fluorescent coating with high luminous efficiency and high bonding strength, and can be applied to the preparation of fluorescent targets for special-shaped parts.

[0010] Specifically, the method for preparing the optical fluorescent target provided by the present invention comprises the following steps: S1, plating aluminum on the metal substrate, and then performing annealing heat treatment to form the Fe-Al alloy transition layer on the metal substrate; S2, performing thermal oxidation treatment in an inert atmosphere to form the aluminum oxide layer; S3, dipping or spraying a sol-gel solution on the surface of the aluminum oxide layer, drying in air, and then sintering under vacuum conditions to obtain the rare earth-doped aluminum oxide coating.

[0011] In step S1, before the aluminum plating, the metal substrate is also subjected to the steps of grinding, polishing and ultrasonic cleaning in sequence, wherein the ultrasonic cleaning is carried out in deionized water, alcohol and acetone in sequence.

[0012] In step S1, the aluminum plating method is room temperature molten salt aluminum plating, embedded aluminum plating or hot dip aluminum plating; The annealing heat treatment conditions are: thermal annealing at 700-1200° C. in a vacuum or argon atmosphere.

[0013] In step S3, the vacuum sintering conditions are as follows: sintering at 400-450° C. under vacuum conditions for more than 30 min.

[0014] In step S3, the preparation method of the sol-gel solution is as follows: Aluminum nitrate and the nitrate of the rare earth element are dissolved in water, and ammonia water is added under stirring to adjust the pH to 4.4-4.6, and then polyvinyl alcohol solution is added to adjust the viscosity to 8-12 mPa·s, and then α-Al2O3 powder is added to obtain the product.

[0015] The grain size of the α-Al2O3 powder is 20 nm-1 μm; The doping amount of the rare earth element is 0.5%-5% of the total mass of the target; The thickness of the rare earth-doped aluminum oxide coating is determined by the number of dipping or spraying. The more times, the thicker the film layer.

[0016] Since the outer electron structure of common rare earth elements is complex and their corresponding electron transition energy levels are relatively more, rare earth elements are more likely to excite fluorescence than pure alumina during ion beam bombardment. Rare earth elements doped in alumina coatings can effectively improve the luminous efficiency of fluorescent targets and greatly increase the sensitivity of ion beam detection and diagnosis.

[0017] The method of the present invention can realize the uniform doping of rare earth elements in alumina at the molecular level. The raw materials used in the sol-gel method are first dispersed in a solvent to form a low-viscosity solution, and the uniformity at the molecular level is obtained in a very short time. When the gel is formed, the incorporated trace elements and reactants are uniformly mixed at the molecular level at the same time.

[0018] The fluorescent coating prepared by the method of the present invention has high structural stability and high bonding strength. The first layer and the second layer are both aluminum oxide. Since they are the same material, there is almost no lattice mismatch phenomenon, and no stress concentration will be generated. After high-temperature sintering, the two have very good bonding strength. Since the second layer of aluminum oxide grows by self-oxidation on the basis of the Fe-Al layer, it has very good compatibility with the Fe-Al layer. The Fe-Al layer is an alloy of aluminum and the base metal, which realizes the metallurgical bonding of the coating and the metal base. Compared with the preparation of fluorescent coating by directly coating rare earth-doped alumina gel on the metal surface, the fluorescent coating prepared by the method of the present invention has very high bonding strength. Moreover, since the mutual matching degree between the layers is high, it is ensured that during the ion beam bombardment process, the thermal expansion coefficient can also maintain good consistency and is not easy to fall off.

[0019] The method of the present invention can also realize the preparation of various special-shaped fluorescent targets. In each key process of preparing the fluorescent coating, such as embedded aluminum, hot dip plating, room temperature molten salt aluminum plating, sol-gel dipping or spraying, it can be realized on the surface of the target body of any shape without being restricted by the shape. Special-shaped fluorescent targets can be prepared according to the specific requirements of different experiments.

[0020] The method provided by the present invention can be used to prepare a fluorescent target with high luminous efficiency, good fluorescent layer bonding force and special shape and structure, thereby meeting the demand for special fluorescent targets in ion beam precision experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of rare earth doped aluminum oxide fluorescent coating.

[0022] Figure 2 This is the process flow chart of rare earth doped alumina fluorescent coating.

[0023] Figure 3 This is a physical picture of the rare earth-doped aluminum oxide fluorescent coating on the inner concave surface.

[0024] Figure 4 Scanning electron microscope photograph of Eu-doped alumina fluorescent coating prepared by sol-gel method and key element mapping distribution diagram.

[0025] Figure 5 These are photos of fluorescent targets irradiated by 5 MeV Xe ions, where (a) shows a Eu-doped alumina fluorescent layer target and (b) shows an ordinary alumina fluorescent layer target. DETAILED DESCRIPTION

[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0027] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0028] according to Figure 2 The flowchart shown is for preparing fluorescent targets.

[0029] Preparation of sol-gel solution: 10 g of Al(NO3) 3· 9H2O and 1.5 g of Eu(NO3) 3· 6H2O was dissolved in 150 ml of distilled water, and ammonia was added dropwise under stirring to adjust the pH of the solution to 4.5. The blue-white suspension was then stirred and refluxed at 75°C and 500 rpm for 20 h. The sol was then cooled to room temperature and the viscosity was adjusted to 10 mPa·s by adding polyvinyl alcohol solution. Then 12.5 wt% of α-Al2O3 powder with a particle size of 20 nm was added to the sol.

[0030] The concave stainless steel substrate was ground and polished. Then it was ultrasonically cleaned with ethanol and acetone, and aluminum was plated by embedding infiltration. After aluminum plating, it was thermally annealed at 1000 °C for 9 h under vacuum conditions to allow aluminum to penetrate into the metal matrix, forming a FeAl2 alloy in the stainless steel matrix. Then, it was oxidized and heat treated for 80 h in an argon atmosphere with an oxygen partial pressure of 2 Pa, and finally a dense polycrystalline aluminum oxide layer was formed on the surface. The thickness of the FeAl2 alloy layer was 50 μm, and the thickness of the aluminum oxide was 200 nm.

[0031] The sol-gel solution prepared above was impregnated on the surface of the polycrystalline alumina layer. The impregnated sample was dried in air. Different impregnation times were selected according to the desired thickness of the alumina layer. In this embodiment, the sample was impregnated twice, and after being completely dried, it was sintered at 400 °C under vacuum conditions for 30 min. Finally, a Eu-doped alumina fluorescent coating was successfully prepared on the inner concave metal substrate. Figure 3 As shown, its thickness is about 20 μm.

[0032] The structural schematic diagram of the rare earth doped aluminum oxide fluorescent coating prepared in this embodiment is shown in FIG. Figure 1 shown.

[0033] Figure 4 The scanning electron microscope photo of the Eu-doped alumina fluorescent coating and the key element mapping distribution diagram show that the surface of the fluorescent coating is obtained by combining granular alumina, Al and O are evenly distributed on the coating, and Eu is successfully doped into the alumina coating with a doping amount of 2 wt%.

[0034] In order to test the luminescence performance of the Eu-doped aluminum oxide fluorescent layer prepared in this example, a Xe irradiation with an energy of 5 MeV and a current of 1 μA provided by the 320 keV heavy ion irradiation platform of the Institute of Modern Physics, Chinese Academy of Sciences was used. 20+ The fluorescent layer was bombarded with a heavy ion beam and compared with a FeAl2 alumina fluorescent target without rare earth element doping (referring to a fluorescent target that was only aluminum-plated, thermally annealed, and thermally oxidized but not impregnated). Figure 5 The fluorescence intensity comparison photos of two aluminum oxide target sheets during heavy ion beam irradiation are given. It can be seen that the luminescence intensity and efficiency of the target sheet doped with rare earth elements prepared by the present invention are much higher than those of ordinary target sheets under low energy and low flux irradiation conditions.

Claims

1. A luminescent fluorescent target film, comprising, from bottom to top, a metal substrate, a Fe-Al alloy transition layer, an aluminum oxide layer and a rare earth-doped aluminum oxide coating, which are composited in sequence.

2. The luminescent fluorescent target sheet according to claim 1, characterized in that: The material of the metal substrate is stainless steel or other metals with good thermal conductivity; The thickness of the Fe-Al alloy transition layer is 8-500 μm; The thickness of the aluminum oxide layer is 100-1000 nm; The rare earth doped aluminum oxide coating has a thickness of 10 μm-500 μm.

3. The luminescent fluorescent target sheet according to claim 1 or 2, characterized in that: The rare earth element doped in the rare earth doped alumina coating is at least one of Eu, Er, Nd and Sm.

4. The method for preparing the fluorescent target sheet according to any one of claims 1 to 3, comprising the following steps: S1, plating aluminum on the metal substrate, and then performing annealing heat treatment to form the Fe-Al alloy transition layer on the metal substrate; S2, performing oxidation treatment in an inert atmosphere to form the aluminum oxide layer; S3, dipping or spraying a sol-gel solution on the surface of the aluminum oxide layer, drying in air, and then sintering under vacuum conditions to obtain the rare earth-doped aluminum oxide coating.

5. The preparation method according to claim 4, characterized in that: In step S1, before the aluminum plating, the metal substrate is also subjected to the steps of grinding, polishing and ultrasonic cleaning in sequence, wherein the ultrasonic cleaning is carried out in deionized water, alcohol and acetone in sequence.

6. The preparation method according to claim 4 or 5, characterized in that: In step S1, the aluminum plating method is room temperature molten salt aluminum plating, embedded aluminum plating or hot dip aluminum plating; The annealing heat treatment conditions are: thermal annealing at 700-1200° C. in a vacuum or argon atmosphere.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S3, the vacuum sintering conditions are as follows: sintering at 400-450° C. under vacuum conditions for more than 30 min.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step S3, the preparation method of the sol-gel solution is as follows: Aluminum nitrate and the nitrate of the rare earth element are dissolved in water, and ammonia water is added under stirring to adjust the pH to 4.4-4.6, and then polyvinyl alcohol solution is added to adjust the viscosity to 8-12 mPa·s, and then α-Al2O3 powder is added to obtain the product.

9. The preparation method according to claim 8, characterized in that: The doping amount of the rare earth element is 0.5%-5% of the total mass of the target; The particle size of the α-Al2O3 powder is in the range of 10 nm to 1 μm.

10. The preparation method according to any one of claims 4 to 9, characterized in that: The dipping or spraying step in step S3 is performed 2-5 times.

Citation Information

Patent Citations

  • Real-time diagnosis system for section of accelerator particle beam

    CN104597476A

  • Fluorescent screen and preparation method thereof

    CN114944314A

  • Radiation-resistant and high-temperature-resistant fluorescent target for high-power beam monitoring

    CN118330707A

  • Radiographic image conversion method

    JP1980012142A

  • Manufacture of radiation picture image converting panel

    JP1989018100A